Rhetoric in classical historiography : four studies - Woodman, A. J. (Anthony John), 1945- (Croom Helm ; Areopagitica Press, 1988)
Professor Woodman's radical study argues against the view that the historian's craft has remained largely unchanged since classical times. A thought-provoking discussion of ancient historiographical theory.